The bladder is an unreliable witness: The case for urodynamic investigations in female stress urinary incontinence. (January 2020) - Serati, Maurizio; Tarcan, Tufan; Finazzi-Agrò, Enrico; Soligo, Marco; Braga, Andrea; Athanasiou, Stavros; Balzarro, Matteo
Abstract: For some years, the role of urodynamics (UDS) in female stress urinary incontinence (SUI) has been a topic of intense debate. The findings of the VaLUE and VUSIS-II randomised clinical trials (RCTs) published in 2012 appeared to suggest that UDS is not useful in women with uncomplicated SUI, with the result that several authoritative guidelines were amended and the routine use of UDS in this setting fell sharply. However, many experts have raised concerns about the design of these two RCTs and their subsequent interpretation – including the inappropriate generalisation of the findings beyond uncomplicated cases, which represent only a small minority of the overall patient population. In this paper, we consider a range of issues and confounding factors which raise doubts about how influential these RCTs should have been and reflect on the potential value of UDS both for objective diagnosis and patient counselling in female SUI.